Oral Presentations 1981
DOI: 10.1055/s-0038-1652237
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-Induced Responses In Human Platelets Differ In Their Requirement For Receptor Occupancy; Evidence For Tight Coupling Between Occupancy And Formation Of Phos- Phatidic Acid

Abstract: Thrombin causes secretion of dense granule constituents from platelets. The time course and extent of this response is unaltered if thrombin is rapidly neutralized after secretion has started, indicating that a sustained occupancy of the thrombin receptors is not required.Using a 50-fold excess of hirudin to neutralize thrombin, we show here that the shape change and aggregation responses also are independent on sustained receptor occupancy. In contrast, the secretion of acid hydrolases, liberation of [3H-]ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 0 publications
6
20
0
Order By: Relevance
“…Pos sibly, they have not taken into account the special conditions mentioned. Holmsen et al [7] reported that, in contrast to the thrombininduced depletion of dense granules, the re lease of a-granule constituents could be im mediately stopped by hirudin. These differ ences may be due to the different velocities of the two processes with the consequence that the velocity of thrombin blockade was just sufficient for interruption of the compara tively slow a-granule secretion process [1,6], Our results are in contradiction to the concept of Martin et al [14] that the dense granule secretion is a thrombin-independent step beginning after the termination of the catalytic step.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pos sibly, they have not taken into account the special conditions mentioned. Holmsen et al [7] reported that, in contrast to the thrombininduced depletion of dense granules, the re lease of a-granule constituents could be im mediately stopped by hirudin. These differ ences may be due to the different velocities of the two processes with the consequence that the velocity of thrombin blockade was just sufficient for interruption of the compara tively slow a-granule secretion process [1,6], Our results are in contradiction to the concept of Martin et al [14] that the dense granule secretion is a thrombin-independent step beginning after the termination of the catalytic step.…”
Section: Discussionmentioning
confidence: 99%
“…Although plate lets were prevented from being activated [11], dense granule secretion was little or not affected by addition of hirudin after secretion was on its way [3,7,15], In this context, it has to be taken into consideration that the kinetics of thrombin-platelet reaction and its inhibition deviate in several aspects from the Michaelis-Menten kinetics valid for common enzymatic reactions. The soluble enzyme reacts with the substrate fixed on the platelet surface.…”
Section: Introductionmentioning
confidence: 99%
“…In resting cells [2] as well as in stimulated cells [3][4][5], evidence has been presented for multiple metabolic pools of phosphoinositides. In platelets the existence of distinct metabolic Abbreviations: PI, phosphatidylinositol; PIP, phosphatidylinositol 4-phosphate; PIP2, phosphatidylinositol 4,5-bisphosphate; PA, phosphatidic acid; GroPI, diacylated phosphatidylinositol pools of PA, PI and PIP2 has been suggested [6][7][8]. Recently, Vickers and Mustard studied the specific [32p]Pi and [3Hlglycerol labelling of the phosphoinositides in both resting and stimulated platelets and proposed separate pools of polyphosphoinositides [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The secretion of [ 14 C]serotonin from platelets was determined by centrifuging the samples at 12,000 g for 2 min and by assaying a 100 Al aliquot of the supernatant by liquid-scintillation counting. Percent [ 14 C] serotonin secretion was determined as described by Holmsen et al (Holmsen et al, 1981).…”
Section: Platelet Aggregation and Serotonin Secretion Assaymentioning
confidence: 99%